The Implementation of Ethnomathematics to Improve Cognitive Learning Outcomes on Integer Topics - Yusrianto Yusrianto; Syamsulrizal; Heny Sri Astutik (Universitas Muhammadiyah Malang, 2026)
This study aims to explore the implementation of ethnomathematics in teaching integer concepts and to describe how this implementation supports the cognitive learning outcomes of seventh-grade students at SMP An-Nur Teminabuan. The study employed a Mixed Methods approach using an Embedded Mixed Methods (QUAL(quan)) design, in which the qualitative approach served as the primary method and the quantitative approach functioned as a supporting method. Qualitative data were collected through observations, interviews, and documentation, while quantitative data were obtained from students’ cognitive learning achievement tests. Qualitative data were analyzed using the interactive analysis model, whereas quantitative data were analyzed descriptively using the mean, maximum score, minimum score, and standard deviation. The findings revealed that the implementation of ethnomathematics was categorized as excellent, as indicated by the teacher’s successful integration of local cultural elements into the learning process and the high level of student engagement during classroom activities. Students demonstrated positive responses to ethnomathematics-based learning because the instructional materials were closely related to their cultural experiences. The test results showed that students achieved good cognitive learning outcomes, with a mean score of 81.73, a maximum score of 95, a minimum score of 60, and a standard deviation of 8.42. The integration of qualitative and quantitative findings indicates that ethnomathematics supports students’ cognitive learning outcomes by providing meaningful learning contexts, increasing student engagement, and strengthening conceptual understanding of integer concepts. Therefore, ethnomathematics can serve as an effective alternative instructional approach for creating contextualized, meaningful mathematics learning experiences that are aligned with students’ local cultural characteristics.